Molecular Dynamics of XFEL-Induced Photo-Dissociation, Revealed by Ion-Ion Coincidence Measurements - Kukk E; Motomura K; Fukuzawa H; Nagaya K; Ueda K (MDPI AG, 2022)
X-ray free electron lasers (XFELs) providing ultrashort intense pulses of X-rays have proven to be excellent tools to investigate the dynamics of radiation-induced dissociation and charge redistribution in molecules and nanoparticles. Coincidence techniques, in particular multi-ion time-of-flight (TOF) coincident experiments, can provide detailed information on the photoabsorption, charge generation, and Coulomb explosion events. Here we review several such recent experiments performed at the SPring-8 Angstrom Compact free electron LAser (SACLA) facility in Japan, with iodomethane, diiodomethane, and 5-iodouracil as targets. We demonstrate how to utilize the momentum-resolving capabilities of the ion TOF spectrometers to resolve and filter the coincidence data and extract various information essential in understanding the time evolution of the processes induced by the XFEL pulses.